Europa Clipper Mission Concept: Exploring Jupiter's Ocean Moon. Issue 20 (20th May 2014) - Phillips, Cynthia B.; Pappalardo, Robert T.
<x xml:space="preserve">Abstract</x> The ice‐covered world Europa—one of the four large Galilean satellites of Jupiter—may be the best place in the solar system to look for currently existing life beyond Earth.